CFTR protects against vascular inflammation and atherogenesis in apolipoprotein E-deficient mice. Issue 4 (7th July 2017) - Li, Zhengzhang; Shen, Zhe; Xue, Haoping; Cheng, Shi; Ji, Qun; Liu, Yutan; Yang, Xiangjun
Abstract : Atherosclerosis is a chronic inflammatory disease of the vascular wall. Dysfunction of cystic fibrosis transmembrane conductance regulator (CFTR) has been shown to result in inflammatory responses in cystic fibrosis (CF) patients. However, little is known about the role of CFTR in vascular inflammation and atherogenesis. Our results showed that CFTR was dominantly expressed in macrophages of atherosclerotic plaque and reduced in aorta and aortic sinus from atherosclerotic apolipoprotein E-deficient (apoE −/− ) mice. In vivo administration of adenovirus encoding CFTR (Ad-CFTR) with apoE −/− mice fed on high-fat diet (HFD) improved plaque stability by decreasing lipid accumulation and necrotic area and increasing smooth muscle cell content and collagen. The Ad-CFTR-treated mice also displayed reduced proinflammatory cytokines levels in aorta and peritoneal macrophages, whereas the anti-inflammatory M2 macrophage markers were increased. Confocal microscopy revealed that the infiltration of T lymphocytes, neutrophils, and macrophages in aortic sinus was markedly attenuated in Ad-CFTR-treated apoE −/− mice. Moreover, in vitro experiments showed that overexpression of CFTR inhibited ox-LDL-induced the migration of peritoneal macrophages. Finally, it was observed that CFTR up-regulation suppressed NFκB and MAPKs activity induced by ox-LDL. Inhibition of JNK or ERK abrogated CFTR down-regulation induced NFκB activation, whereas NFκB inhibitor had no effect on JNK or ERK activation. Taken together, these results demonstrate that CFTR prevents inflammation and atherogenesis via inhibition of NFκB and MAPKs activation. Our data suggest that CFTR may present a potential therapeutic target for the treatment of vascular inflammation and development of atherosclerotic disease.